2006
DOI: 10.1177/1038411106061508
|View full text |Cite
|
Sign up to set email alerts
|

The impact of organisational values and performance management congruency on satisfaction and commitment

Abstract: The relationship between organisational values and performance management systems and the influence this relationship has on an employee's job satisfaction and commitment was investigated surveying 325 employees from an Australian public service organisation. Respondents were classified into four main value types -Collegial, Meritocratic, Leadership and Elite, according to a typological theory of organisational values. Factor analysis of the performance management items revealed two core dimensions -compensati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Furthermore, other HILDA research also indicates a positive association between hours worked and job satisfaction, expressed by "over-workers" who exceed standard work hours and, perhaps paradoxically, resent working extra hours (Fabian & Breunig, 2019). between their values and their organizations' values influences their commitment to the organization (Abbott, White, & Charles, 2005;Howell, Kirk-Brown, & Cooper, 2012;Rosete, 2006) and job satisfaction and intention to stay (Newton & Mazur, 2016). Workers' commitment is diminished when organizations fail to enact espoused values (Howell et al, 2012).…”
Section: Measurement Properties Of the Dws In Different Nationsmentioning
confidence: 98%
“…Furthermore, other HILDA research also indicates a positive association between hours worked and job satisfaction, expressed by "over-workers" who exceed standard work hours and, perhaps paradoxically, resent working extra hours (Fabian & Breunig, 2019). between their values and their organizations' values influences their commitment to the organization (Abbott, White, & Charles, 2005;Howell, Kirk-Brown, & Cooper, 2012;Rosete, 2006) and job satisfaction and intention to stay (Newton & Mazur, 2016). Workers' commitment is diminished when organizations fail to enact espoused values (Howell et al, 2012).…”
Section: Measurement Properties Of the Dws In Different Nationsmentioning
confidence: 98%
“…The P–O fit can predict outcomes such as adjustment, job satisfaction, organisational commitment, intention to stay and tenure, as well as affecting communication by reducing ambiguity and conflict (Meglino & Ravlin , Parkes et al . , Rosete ). Meglino and Ravlin () suggest that people who hold similar values and goals view the world in similar ways, enabling them to communicate more clearly, anticipate each other's behaviour and coordinate activities more efficiently – all of which result in reduced role conflict and ambiguity and higher satisfaction with interpersonal relationships.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies exploring the association between OV and OC were found. Rosete () examined the association between organisational values, human resource management and OC among 325 employees of an Australian public service organisation, finding that individuals who work in environments where a fit exists between OV and performance management systems have a greater level of commitment than other individuals. A relationship between OV and OC was also found in studies among 387 transportation executives (Boxx et al .…”
Section: Introductionmentioning
confidence: 99%
“…Festinger's (1962) Theory of Cognitive Dissonance holds that individuals strive to minimize dissonance in their environment and that continued dissonance leads to dissatisfaction. This assertion is supported by a substantial body of research work (Adkins et al, 1996;Amos and Weathington, 2008), although some evidence fails to support this relationship (Rosete, 2006). However, on the balance of existing empirical evidence, we suggest that employees who perceive poor fit with the organization in terms of their values and goals would therefore be dissatisfied in their jobs.…”
Section: Hypothesesmentioning
confidence: 68%